2021
DOI: 10.1097/gme.0000000000001704
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial predictors of depressive symptoms in the perimenopause—findings from the Swiss Perimenopause Study

Abstract: Objective: The perimenopause is associated with increased hormone fluctuations and an elevated risk of depression. A number of predictors of depressive symptoms in the menopausal transition have previously been suggested. The purpose of this study was to investigate a set of biopsychosocial predictors of depressive symptoms in perimenopausal women. Methods: This cross-sectional study, investigating 114 perimenopausal women (according to the STRAW criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…Having persistent and/or troublesome VMS and sleep problems can make women feel stressed and irritable, which in turn can exacerbate menopausal symptoms. An estimated 9–10% of women report an increase in psychological symptoms, including depressed mood and/or anxiety, during the menopause transition (Almeida et al, 2016 ; Mishra & Kuh, 2012 ), which tends to be relatively transient, and is associated with troublesome VMS, current stress, low self‐esteem, and hormone fluctuations (Arnot, Emmott, & Mace, 2021 ; Campbell, Dennerstein, Finch, & Szoeke, 2017 ; Willi, Süss, Grub, & Ehlert, 2021 ). Longer duration of VMS has been linked with higher levels of perceived stress (Avis et al, 2015 ); acute psychological stress has been shown to provoke VMS (Swartzman, Edelberg, & Kemmann, 1990 ); there is also some evidence of altered physiological stress responsivity in women with VMS (Nathan et al, 2020 ).…”
Section: Figurementioning
confidence: 99%
“…Having persistent and/or troublesome VMS and sleep problems can make women feel stressed and irritable, which in turn can exacerbate menopausal symptoms. An estimated 9–10% of women report an increase in psychological symptoms, including depressed mood and/or anxiety, during the menopause transition (Almeida et al, 2016 ; Mishra & Kuh, 2012 ), which tends to be relatively transient, and is associated with troublesome VMS, current stress, low self‐esteem, and hormone fluctuations (Arnot, Emmott, & Mace, 2021 ; Campbell, Dennerstein, Finch, & Szoeke, 2017 ; Willi, Süss, Grub, & Ehlert, 2021 ). Longer duration of VMS has been linked with higher levels of perceived stress (Avis et al, 2015 ); acute psychological stress has been shown to provoke VMS (Swartzman, Edelberg, & Kemmann, 1990 ); there is also some evidence of altered physiological stress responsivity in women with VMS (Nathan et al, 2020 ).…”
Section: Figurementioning
confidence: 99%
“…Recent findings suggest highly individual fluctuations in E2 and progesterone during perimenopause ( 6 , 9 , 11 ). As such, the current results are consistent with previous findings of fluctuating secretion patterns of sex steroids during perimenopause, and contradict findings of a continuous decline due to the perimenopausal transition ( 4 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Swiss Perimenopause Study addresses these limitations by employing closely spaced, longitudinal, and continuous measurements within highly standardized assessments of endocrine changes, measuring E2, progesterone, and cortisol several times for three non-consecutive months over the course of 1 year in solely perimenopausal women. Based on a recent cross-sectional study conducted by our work group ( 11 ), which reported fluctuations in E2 and progesterone levels even within one month, the aim of the present study is to contribute to a better understanding of the specific perimenopausal secretion patterns of steroid hormones by illustrating the fluctuations of E2, progesterone, and cortisol longitudinally and continuously over the course of 1 year in 127 perimenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is its interaction with GABA receptors [ 75 ]. Likewise, in premenopausal depressive disorder, progesterone levels remain constant [ 76 ] but E2 stands out when its levels are higher, assuming a direct risk of the intensification of depressive symptoms at this stage [ 77 ].…”
Section: Major Depressive Disorder In Womenmentioning
confidence: 99%